ISPC Commentary on the Proposal for CRP2 - March 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the proposal for CRP 2: Policies, Institutions and Markets to Strengthen Food Security and Incomes for the Rural Poor (Version of January 2011).